Estudo de Estrutura Eletrônica de Nanofitas de Nitreto de Boro utilizando Cálculos de Primeiros Princípios - Frazão, Nilton Ferreira (2009)
Recently, the existence of nanoribbon of Boron Nitride with finite size was discovered experimentally, in porous nanoesferas of BN (100-400 nm of diameter), synthesized for the reaction of B2O3 with carbon spheres contend nanoporos filled for Nitrogen to a temperature of 17500C. However a theoretical inquiry of the properties of this nanometerial did not exist. Then, in this present work, we carry through simulation of molecular mechanics using field of universal force (forcefild) to optimize the structure of some of these nanoribbon of Boron Nitride, with objective to find a conformation more steady, that is, of lesser energy for these nanostructures. Later, we investigate the electronic properties of these nanoribbon of Boron Nitride (NRBN) in the finite form (not-periodic) of two types: nanoribbon of Boron Nitride of the type to armchair (a-NRBN) and nanoribbon of Boron Nitride of the type zigzag (z-NRBN). The study of these properties they had been carried through of calculations of first principles based in the Density Functional Theory, with the local density approximation (LDA). Through our calculations, we observe that all the nanoribbon are metallic when we made the analysis of the density of states (DOS). Result not waited, but surprising, therefore of literature we know that material nanostructuralized of Boron Nitride they are always semiconductors. However, our calculations had shown that as much a-NRBN as z-NRBN had presented a conducting electronic character. The simulations had been carried through for many cases of nanoribbon of width (L) and length (C), forming a pair of indices (L, C), with the objective to facilitate the identification of these nanostructures. However we will present the results of but twelve of these, being: (1,3), (1,6), (1,9), (2,3), (2,6) e (2,9) in such a way of the types a-NRBN and z-NRBN.